2023
DOI: 10.55549/jeseh.1239074
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Experimental Studies on STEM Education

Abstract: This research systematically examines the experimental articles on STEM education (science, technology, engineering, and mathematics education). In this direction, experimental articles with the Social Sciences Citation Index on the Web of Science were analyzed within the scope of research questions, taking into account the guidelines of PRISMA. The research was carried out using the systematic review method. In the first search made in this line, the results listed 17,482 studies. Then, this number was reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…For the last decade, there has been an increase in experimental researches in relation to the influences and impacts of the SP-STEAM oriented education, except for the period encompassing the pandemic. Consideration in this context reveals that the findings of many studies displayed parallelism with this study [11,24,26,27], which emphasizes the validity and reliability of the current research.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…For the last decade, there has been an increase in experimental researches in relation to the influences and impacts of the SP-STEAM oriented education, except for the period encompassing the pandemic. Consideration in this context reveals that the findings of many studies displayed parallelism with this study [11,24,26,27], which emphasizes the validity and reliability of the current research.…”
Section: Discussionsupporting
confidence: 75%
“…Teachers have been considered as the most crucial part of STEAM education. A very recent study which systematically reviewed experimental studies regarding STEAM applications worldwide reported that 95% of experiments have first concentrated on training teachers prior to any treatment application, and summarized that any application without training of teachers would not be effective [11]. While studies report that experimental studies regarding STEAM education will mostly fail without in-service teacher training, the question arises as to why teachers are found to be inadequate in application of STEAM in classrooms.…”
Section: Introductionmentioning
confidence: 99%
“…This laboratory facilitates the visualization, contextualization, and perception of STEAM theory and practices through interactive teaching projects. The experiment confirms that the laboratory is practical and can enhance learners' comprehensive and practical innovation capabilities [13].…”
Section: The Role Of Vr In Steam Educationsupporting
confidence: 58%
“…However, there are limitations and challenges that need to be considered when implementing VR in STEAM education, such as the availability of VR equipment and cost [2,6,13]. Nonetheless, with proper planning and integration, VR can be a valuable tool for enhancing STEAM education and preparing students for the digital age.…”
Section: The Role Of Vr In Steam Educationmentioning
confidence: 99%
See 1 more Smart Citation